STRATEGI PENGEMBANGAN HOMESTAY PADA KAWASAN WISATA DIENG DALAM MENDUKUNG WISATA BERKELANJUTAN: Homestay Development Strategy in The Dieng Tourism Area in Supporting a Sustainable Tourism - Dziefa Ndaru Yuntafa; ayyd namira Riandini; rifa tiara Zahra; Joy gladness; Fetty Nurmala Rossi (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Dieng Kulon is a village located in Dieng High Plains, Wonosobo District. As a tourist village surrounded by popular destinations, Dieng Kulon must have tourist facilities, one of which is tourist accommodation. The aim of this research is to identify how the omestay development strategy in Dieng Kulon Tourism Village supports ustainable tourism. This research method employs qualitative descriptive methods. The survey data was obtained through field surveys, and interviews with community-based tourism institutions, homestay managers, and tourists. This study is also supplemented with SWOT analysis. The results are obtained that the Dieng Area has already inhabited 9 ASEAN Homestay Criteria with its inhabitants 9 The above criteria will make a Tourist Village Area that continues to be sustainable through 3 priciples of sustainability aspects of tourismuch as the principles of environmental aspects, principles economic aspectsnd principles social and cultural aspects. So the strategy used by Homestay on Tourist Areas Dieng in Supporting Sustainable Tourism is the strategy of SO, that is to exploit local events in attracting tourists to stay in the homestay. Social media promotions and online platforms help tourists find and choose heir accommodation